Measurement of CP violation in B0 → D+D− and B0S → D+sD-s decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2025)
A time-dependent, flavour-tagged measurement of CP violation is performed with B0 → D+D− and $$ {B}_s^0 $$→ $$ {D}_s^{+}{D}_s^{-} $$decays, using data collected by the LHCb detector in proton-proton collisions at a centre-of-mass energy of 13 TeV corresponding to an integrated luminosity of 6 fb−1. In B0 → D+D− decays the CP-violation parameters are measured to beSD+D−=−0.552±0.100stat±0.010syst,CD+D−=0.128±0.103stat±0.010syst.$$ {\displaystyle \begin{array}{c}{S}_{D^{+}{D}^{-}}=-0.552\pm 0.100\left(\textrm{stat}\right)\pm 0.010\left(\textrm{syst}\right),\\ {}{C}_{D^{+}{D}^{-}}=0.128\pm 0.103\left(\textrm{stat}\right)\pm 0.010\left(\textrm{syst}\right).\end{array}} $$